The prince and the pauper - Twain, Mark (Boston, Mass : Thomson Heinle, 2007)
When young Edward VI of England and a poor boy who resembles him exchange places, each learns something about the other's very different station in life
Title from container
Keywords: Edward -- VI, -- King of England, -- 1537-1553 -- Juvenile fiction; American literature; Mistaken identity -- Fiction; Adventure and adventurers -- Fiction